Taxonomy, chemodiversity, and chemoconsistency of Aspergillus, Penicillium, and Talaromyces species - Frisvad, Jens C. (Frontiers in Microbiology, 2015)
Aspergillus, Penicillium and Talaromyces are among the most chemically inventive of all fungi, producing a wide array of secondary metabolites (exometabolites). The three genera are holophyletic in a cladistic sense and polythetic classes in an anagenetic or functional sense, and contain approximately 300, 500 and 120 species, respectively. New developments in classification, cladification and nomenclature have meant that the species, series and sections are natural groups that share many extrolites, including exometabolites, exoproteins, exocarbohydrates and exolipids in addition to morphological features. The number of secondary metabolites reported from these species is very large, and genome sequencing projects have shown that a large number of additional exometabolites may be expressed, given the right conditions (“silent” gene clusters for exometabolites). The exometabolites are biosynthesized via shikimic acid, tricarboxylic acid cycle members, nucleotides, carbohydrates, or as polyketides, nonribosomal peptides or mixtures of those. The gene clusters coding for these compounds contain genes for the biosynthetic building blocks, the linking of these building blocks, tailoring enzymes, resistance for own products, and exporters. Species within a series or section in Aspergillus, Penicillium and Talaromyces have many exometabolites in common, seemingly acquired by cladogenesis, but many autapomorphic exometabolites may have been acquired by horizontal gene transfer. Despite genome sequencing efforts, and the many break-throughs these will give, it is obvious that epigenetic factors play a large role in evolution and function of chemodiversity, and better methods for characterizing the epigenome are needed. Most of the individual species of the three genera produce a consistent and characteristic profile of exometabolites, but epigenetic and growth medium variations, stimulation by exometabolites from other species, and variations in abiotic intrinsic and extri